2005
DOI: 10.1080/10242690500114751
|View full text |Cite
|
Sign up to set email alerts
|

Military Expenditure and Economic Growth in Middle Eastern Countries: A Dynamic Panel Data Analysis

Abstract: Defence expenditures have both costs and benefits to the economy. The costs of defence expenditures are mainly emphasized as opportunity costs. On the other hand, defence spending may have growth-promoting potential benefits: a rise in defence spending may result in a higher aggregate demand, production and employment. This paper examines empirically the effects of military expenditures on economic growth for Middle Eastern countries and Turkey, for the time-period 1989-1999. The relationship between military … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
78
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 163 publications
(85 citation statements)
references
References 27 publications
7
78
0
Order By: Relevance
“…These findings are consistent with the existing literature such as Khilji and Mahmood (1997), Atesoglu (2002), Karagol and Palaz (2004), Smith and Tuttle (2008), Tang (2008) and Keller et al (2009). The estimated coefficient of government non-military spending is showing positive impact on economic growth supporting the views of Halicioglu (2004), Yildirim et al (2005) and Wijeweera and Webb (2009). The inverse relationship is also witnessed between real interest rate and economic growth, and is consistent with findings of Halicioglu (2004).…”
Section: Conclusion and Policy Implicationssupporting
confidence: 82%
See 4 more Smart Citations
“…These findings are consistent with the existing literature such as Khilji and Mahmood (1997), Atesoglu (2002), Karagol and Palaz (2004), Smith and Tuttle (2008), Tang (2008) and Keller et al (2009). The estimated coefficient of government non-military spending is showing positive impact on economic growth supporting the views of Halicioglu (2004), Yildirim et al (2005) and Wijeweera and Webb (2009). The inverse relationship is also witnessed between real interest rate and economic growth, and is consistent with findings of Halicioglu (2004).…”
Section: Conclusion and Policy Implicationssupporting
confidence: 82%
“…It is found that a 5% increase in non-military expenditures raises economic growth by 0.649%. The findings are consistent with existing defence economics literature including Atesoglu (2002) for the USA, Halicioglu (2004) for Turkey, Yildirim et al (2005) for Middle Eastern countries, Tang (2008) for Malaysia and Wijeweera and Webb (2009) for Sri Lanka. Finally, real interest rate is inversely correlated with economic growth.…”
Section: Empirical Estimationsupporting
confidence: 80%
See 3 more Smart Citations